2003
DOI: 10.1111/j.1365-2133.2003.05549.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pityriasis versicolor in young Italian sailors

Abstract: The prevalence of pityriasis versicolor in this sample of young Italian sailors was not high, in agreement with the available surveys performed in the general population in temperate climates. Many affected subjects were not aware of their condition. The only important factor associated with pityriasis versicolor was a previous history of pityriasis versicolor. This observation could confirm the hypothesis that constitutional factors, e.g. seborrhoea and chemical constitution of sebum, may play a crucial role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
7
3
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
4
7
3
1
Order By: Relevance
“…Since pityriasis versicolor is commoner in young adults, students were found to be the most commonly affected ones in our study. Majority (52.73%) of our study population were asymptomatic, as also reported by Razack AE et al 9 and Ingordo et al 10 In our study, 48.18% patients had history of recurrences, which has also been documented by Krishnan et al 8 Seasonal trend was found in our study as most of the cases presented in the month of August and September. In the study of Dutta et al ,6 most of the cases presented in the month of July to September and Rao et al ,7 also revealed clustering of cases (35%) during the summer months.…”
Section: Discussionsupporting
confidence: 88%
“…Since pityriasis versicolor is commoner in young adults, students were found to be the most commonly affected ones in our study. Majority (52.73%) of our study population were asymptomatic, as also reported by Razack AE et al 9 and Ingordo et al 10 In our study, 48.18% patients had history of recurrences, which has also been documented by Krishnan et al 8 Seasonal trend was found in our study as most of the cases presented in the month of August and September. In the study of Dutta et al ,6 most of the cases presented in the month of July to September and Rao et al ,7 also revealed clustering of cases (35%) during the summer months.…”
Section: Discussionsupporting
confidence: 88%
“…No association was found between pityriasis versicolor and sporting activities or marching 15. Alopecia areata was the diagnosis in 5.4% of military personnel, which was significantly higher than in civilians: the rate was 2.1% in a military study from Saigon, Vietnam, in 1967 8…”
Section: Discussionmentioning
confidence: 92%
“…7,8,9,19 Ingordo, studying a group of Italian sailors, found a significant association of past history of the disease in individuals with pityriasis versicolor, backing the hypothesis that constitutional factors may be important in the pathogenesis of this dermatosis. 20 In relation to symptoms, the frequency of asymptomatic individuals and those complaining of pruritus was similar. This finding is consistent with most studies that define the disease as asymptomatic or oligosymptomatic.…”
Section: Discussionmentioning
confidence: 93%